Peranan Refleksi Harian Dalam Pengembangan Profesionalisme Guru Pada Kegiatan PPL Mahasiswa STAB Kertarajasa, Tahun Akademik 2024/2025 Di SD My Little Island Malang - Priadi Priadi (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
The purpose of this study was to describe the role of daily reflection in the development of teacher professionalism in the Field Experience (PPL) practice of STAB Kertarajasa teachers at My Little Island Elementary School, Malang. The research methodology used was a qualitative descriptive approach with data collection techniques in the form of observation, documentation, and interviews. The subjects of the study were four PPL students, one supervising teacher, and one principal. The results of the study indicate that human reflection is very important to improve teacher professionalism, especially in the field of pedagogical competence in this case including evaluating their teaching practices directly and objectively every day. by reflecting, teachers can identify successes and shortcomings in the learning process, understand the responses and needs of students, and find solutions to problems that arise in the classroom. in this process encourages teachers to continue learning, adapting, and improving themselves which are the main characteristics of professionalism. Daily reflection helps PPL students in the following matters: (1) identifying learning difficulties and weaknesses; (2) assessing learning outcomes and implementation; (3) utilizing real things in teaching; and (4) aligning learning methods and media with the needs of students. One of the most popular reflection techniques is the reflection triangle, which helps PPL students analyze the effectiveness of their learning. And Daily Reflection serves as a foundation for teacher professional development because it encourages self-evaluation, improvement, and adaptation to changes in the classroom environment.